2017
DOI: 10.1186/s12906-017-1915-9
|View full text |Cite
|
Sign up to set email alerts
|

The protective effects of Resveratrol against radiation-induced intestinal injury

Abstract: BackgroundIntestinal injury is a potential cause of death after high-dose radiation exposure. The aim of the present study was to investigate the protective effects of resveratrol against radiation-induced small intestine injury.MethodsC57BL/6 N mice were irradiated and treated with resveratrol and/or Ex527 (a potent Sirt1 inhibitor), and subsequent examining intestinal morphological changes, and crypt cell apoptosis. Then, the expression and enzyme activity of SOD2 in the small intestine were examined. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 45 publications
(53 reference statements)
5
44
0
Order By: Relevance
“…It can ameliorate oxidative stress, DNA damage, apoptosis and subsequent consequences following exposure to gamma radiation in mice intestinal tissue. These radioprotective effects are mediated by acetylation of p53 and activation of Sir1, resulting in resistance of intestinal crypt cells to apoptosis [135]. Administering resveratrol before irradiation of rats' abdomen with 10 Gy could ameliorate increased level of inflammatory cytokine, regulatory T cells, and oxidative DNA damage, whereas it increased the white blood cell counts such as CD4+ T cells [136].…”
Section: Resveratrolmentioning
confidence: 99%
“…It can ameliorate oxidative stress, DNA damage, apoptosis and subsequent consequences following exposure to gamma radiation in mice intestinal tissue. These radioprotective effects are mediated by acetylation of p53 and activation of Sir1, resulting in resistance of intestinal crypt cells to apoptosis [135]. Administering resveratrol before irradiation of rats' abdomen with 10 Gy could ameliorate increased level of inflammatory cytokine, regulatory T cells, and oxidative DNA damage, whereas it increased the white blood cell counts such as CD4+ T cells [136].…”
Section: Resveratrolmentioning
confidence: 99%
“…Zhang et al [ 41 ] investigated the effects of resveratrol against radiation-induced small intestine injury in mice. In this study, the mice were pretreated with resveratrol 5 days before and 1 day after prior to a large single dose partial-body (abdominal) irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Under physiological conditions, epithelial homeostasis is maintained by proliferative cells in crypts, and the small intestinal crypt Many studies have shown that IR-induced tissue damage increases the amount of apoptotic cells. [31][32][33] Caspases are a family of genes important for maintaining homeostasis by regulating apoptosis and inflammation. 34 Caspases involved in apoptosis have been subclassified by their mechanism of action into initiator caspases (caspase-8 and -9) and executioner caspases (caspase-3, -6 and -7).…”
Section: Discussionmentioning
confidence: 99%